Pengaruh Kepemilikan Publik, Pertumbuhan Perusahaan, Dan Ukuran Kantor Akuntan Publik Terhadap Penggantian Auditor: Studi pada Perusahaan Indeks Kompas100 Periode 2011-2013 - Michelle Kristian (Jurnal Ekonomi, 2015)
The issue of auditor independence is the main cause why the company is required to conduct mandatory auditor replacement. Various questions arise when there are companies that perform voluntary auditor replacement, the change of auditors outside the Peraturan Menteri Keuangan No. 17/PMK.01/2008. The purpose of this study is to test the effect of public ownership, company growth, and public accountant firms' size on auditor replacement. The object of this study is the Kompas100 Index company for the period 2011-2013. The selection of the sample is determined based on the purposive sampling method. The sample used in the study are 34 companies that are successively entered the Kompas100 Index period 2011-2013 except for the financial sector, presenting financial statements in Indonesian Rupiah, has assets increased from year to year, and contains all data related to all variables. The data used in this study are secondary data, the annual financial statements audited by an independent auditor. The data analysis method used is logistic regression, as the dependent variable is non-metric and the independent variables are a mixture of metric and non-metric. The results of this study are (1) public ownership does not affect replacement auditors significantly, (2) company's growth does not affect replacement auditor significantly, (3) public accountant firm's size does not affect auditor replacement significantly, (4) public ownership, company's growth, and public accountant firm's size simultaneously do not affect auditor replacement significantly.